2007
DOI: 10.1097/mlr.0b013e3180618b55
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interventions on Health-Related Quality of Life Among Persons With Diabetes

Abstract: A variety of interventions can improve HRQL among adults with diabetes, but the magnitude of effects varied with the interventions. The mechanism of these changes needs to be further examined in the future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 52 publications
4
68
0
4
Order By: Relevance
“…Pooled estimates of five RCTs demonstrated that educational interventions significantly improved physical function and mental health and were associated with a decrease in bodily pain [31]. Also, a pooled effect of five pre-versus post-educational interventions showed significantly improved social function, vitality, mental health and a decrease in role limitations due to physical problems [31]. Notably, in the ten identified studies the proportion of non-Whites ranged between 40 and 70%, suggesting that these findings can be relevant also to other ethnic groups.…”
Section: Quality Of Lifementioning
confidence: 98%
See 1 more Smart Citation
“…Pooled estimates of five RCTs demonstrated that educational interventions significantly improved physical function and mental health and were associated with a decrease in bodily pain [31]. Also, a pooled effect of five pre-versus post-educational interventions showed significantly improved social function, vitality, mental health and a decrease in role limitations due to physical problems [31]. Notably, in the ten identified studies the proportion of non-Whites ranged between 40 and 70%, suggesting that these findings can be relevant also to other ethnic groups.…”
Section: Quality Of Lifementioning
confidence: 98%
“…Results of major trials investigating the effect of a number of interventions on quality of life are reported in Table 2. Pooled estimates of five RCTs demonstrated that educational interventions significantly improved physical function and mental health and were associated with a decrease in bodily pain [31]. Also, a pooled effect of five pre-versus post-educational interventions showed significantly improved social function, vitality, mental health and a decrease in role limitations due to physical problems [31].…”
Section: Quality Of Lifementioning
confidence: 98%
“…For patients, it ought to be improved continuously by health care interventions which are qualitative, evidencebased and conform to acceptable standard of practice [4][5][6]. QOL has been variously defined [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The findings regarding improvement of HRQoL are inconsistent in recent trials. However, recent meta-analyses of interventions that led to improved HRQoL in patients with type 2 diabetes also demonstrated that a variety of interventions could improve HRQoL, but that the effects varied with different treatment concepts [25,29]. Meta-analyses of behavioral and educational interventions focused primarily on metabolic control, weight, and physical activity [26 ,27,28,30], whereas recent research also gives evidence of improvements in terms of self-efficacy and psychological variables.…”
Section: Diabetes Mellitus: a Public Health Problemmentioning
confidence: 95%